2016
DOI: 10.1002/2014wr016618
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐discharge rating curves based on satellite altimetry and modeled discharge in the Amazon basin

Abstract: In this study, rating curves (RCs) were determined by applying satellite altimetry to a poorly gauged basin. This study demonstrates the synergistic application of remote sensing and watershed modeling to capture the dynamics and quantity of flow in the Amazon River Basin, respectively. Three major advancements for estimating basin-scale patterns in river discharge are described. The first advancement is the preservation of the hydrological meanings of the parameters expressed by Manning's equation to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 68 publications
1
116
0
1
Order By: Relevance
“…On the other hand, even if discharges are well represented, there are uncertainties related to Manning values and also to river widths and 25 depths derived from HGs, which do not reflect singularities of cross sections such as narrowing or widening of rivers at both gauge and VS locations. Previous studies have demonstrated the large influence of channel geometry and roughness on both amplitude and timing of water levels, especially over the Amazon basin (e.g., Yamazaki et al, 2011;Paiva et al, 2013;Paris et al, 2016;Luo et al, 2017). Moreover, river bed profiles are subject to DEM errors that can hardly be reduced through simple profile-smoothing procedures.…”
Section: Water Levelsmentioning
confidence: 99%
“…On the other hand, even if discharges are well represented, there are uncertainties related to Manning values and also to river widths and 25 depths derived from HGs, which do not reflect singularities of cross sections such as narrowing or widening of rivers at both gauge and VS locations. Previous studies have demonstrated the large influence of channel geometry and roughness on both amplitude and timing of water levels, especially over the Amazon basin (e.g., Yamazaki et al, 2011;Paiva et al, 2013;Paris et al, 2016;Luo et al, 2017). Moreover, river bed profiles are subject to DEM errors that can hardly be reduced through simple profile-smoothing procedures.…”
Section: Water Levelsmentioning
confidence: 99%
“…; Paris et al. ; Garambois et al. ), these methods do not extract information from the actual terrain.…”
Section: Introductionmentioning
confidence: 99%
“…While prior research using remotely sensed data or statistical approaches to investigate river geometry and rating curves has resulted in useful insights and approaches (Getirana et al 2013;Paris et al 2016;Garambois et al 2017), these methods do not extract information from the actual terrain. Relationships obtained from statistical analyses are thus insufficient to depict the unique physiographic characteristics of each channel and remotely sensed imagery only captures part of a transient state of the river system from a top view, which is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite altimetry has already been used for assessing and improving hydrological models. For example, altimetry data were applied on model validation (Neal et al, ; Paiva, Collischonn, et al, ), calibration of water budget parameters (Getirana, ), assimilation for estimating discharge fields (Paiva et al, ), and development of stage‐discharge rating curves (Paris et al, ).…”
Section: Introductionmentioning
confidence: 99%